Effect of pollen source on some characteristics of fruit and pits of olive cultivars ‘Coratina’ and ‘Tanche’ (Latakia University Journal -Biological Sciences Series, 2020)
The research was conducted in 2017, 2018 and 2019 seasons in order to identify the effect of pollen source on some characteristics of fruits and pits of olive cultivars ‘Coratina’ and ‘Tanche’. Fruiting ratio, fruit and pits characteristics resulted from self-open and cross-pollination (controlled pollination) with ‘Khoderi’ and ‘Dermlali’ were studied. Results showed that both cultivars are self-incompatible, and Olive cultivar ‘Khoderi’ was an efficient pollinizer for both cultivars. Pollen source affected 60% of total studied characteristics of fruits and pits of ‘Coratina’, but this effect was limited and low  in ‘Tanche’. Xenia phenomenon might be active in both studied cultivars but its effect is poor and varies depending on cultivar and season. Planting ‘Khoderi’ in ‘Tanche’ orchards could improve fruit uniformity in length, width and weight.